A murine model of subglottic granulation. Issue 4 (15th February 2016) - Ghosh, A; Leahy, K P; Singhal, S; Einhorn, E; Howlett, P; Cohen, N A; Mirza, N
Abstract: Objective: This study aimed to develop a functional model of subglottic stenosis by inducing direct airway irritation in transplanted mouse laryngotracheal complexes. Methods: Laryngotracheal complexes from C57BL/6 mice were harvested and divided into three groups: uninjured, mechanically injured and chemically injured. Donor laryngotracheal complexes from each group were placed in dorsal subcutaneous pockets of recipient mice. Each week, the transplanted laryngotracheal complexes were harvested, and tissues were fixed, sectioned, and stained with haematoxylin and eosin. Representative slides were reviewed by a blinded pathologist, to determine the formation of granulation tissue, and graded as to the degree of granulation formation. Results: Direct airway irritation induced granulation tissue formation under the disrupted epithelium of airway mucosa; this was seen as early as two weeks after chemical injury. Conclusion: Results indicate that granulation tissue formation in a murine model may be an efficient tool for investigating the development and treatment of subglottic stenosis.